Silu sebagai Alat Musik Tradisional Suku Mbojo: Kajian Budaya dan Pelestariannya - Arif Bulan; Nawasyarif Nawasyarif; Tasrif Tasrif; Kasman Kasman (Indo Publishing, 2026)
This study aims to describe the form and characteristics of the traditional musical instrument silu, examine its symbolic meanings and cultural values, and identify its existence and preservation challenges within the Mbojo community in Bima Regency. The study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation involving traditional leaders, traditional artists, and members of the Mbojo cultural community. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings reveal that silu is a traditional wind instrument characterized by its loud and resonant sound and consists of three detachable parts: the upper, middle, and lower sections. These parts contain symbolic meanings related to the structure of the human body and Islamic religious values within the Mbojo community. The middle section contains seven sound holes symbolizing the seven days of the week as a representation of order and balance in life. Silu functions as an accompanying musical instrument in traditional performances such as tari soka, tari manca, and the folk game mpa’a gantao. Beyond its entertainment function, silu also represents the cultural identity of the Bima community. However, its existence currently faces challenges due to modernization, the declining interest of younger generations, and the lack of cultural documentation. Therefore, preservation efforts through cultural education, cultural dialogue, art studio development, and documentation of local traditions are necessary to maintain silu as a cultural heritage of the Mbojo community.